Clinico-Epidemiological Profile of Children Orphaned due to AIDS Residing in Care Giving Institutions in Coastal South India. (3rd November 2019) - Thapar, Rekha; Singha, Meher; Kumar, Nithin; Mithra, Prasanna; Unnikrishnan, Bhaskaran; Holla, Ramesh; Kulkarni, Vaman; Darshan, B. B.; Kumar, Avinash
Abstract : Background . HIV/AIDS has a greater impact on children. Besides being orphaned by the untimely demise of one or both parents due to the disease, these children are more prone for discrimination by the society. Methods . In this cross-sectional study 86 children orphaned by AIDS residing in care giving institutions for HIV positive children in Mangalore were assessed for their clinico-epidemiological profile and nutritional status. Institutional Ethics Committee clearance was obtained before the commencement of the study. The collected data were analyzed using SPSS (Statistical Package for Social Sciences) version 11.5 and the results expressed in mean (standard deviation) and proportions. BMI was calculated and nutritional status assessed using WHO Z scores (BMI for Age) for children between 5 and 19 years separately for boys and girls. Results . The mean age of the children was 13.2 ± 3 years. Majority (n = 56, 65.1%) of the children were double orphans. Most of the children orphaned by AIDS (n = 78, 90.7%) had a history of both the parents being HIV positive. The median CD4 count of participants at the time of our study was 853.5 (IQR 552–1092) cells/microliter. A higher percentage of orphans were malnourished compared to nonorphans. (41.1% vs. 36.7%). All the educational institutions, wherein the children orphaned by AIDS were enrolled, were aware about their HIV status. Five of the participants felt discriminated in their schools. Only two of the participants felt discriminated by their friends because of their HIV status. Conclusion . From our study we draw conclusion that even though the children orphaned due to AIDS are rehabilitated in terms of having shelter and provision of education and health care, much needs to be done in terms of improving the nutritional status of these children and alleviating the discriminatory attitude of the society towards them.